Elisitasi Kebutuhan Untuk Meningkatkan Kepuasan Pengguna Pada Sistem E-Learning Universitas Muhammadiyah Malang - Muchammad Romadhoni; Wahyu Andhyka Kusuma (Fakultas Teknik Universitas Hamzanwadi, 2021)
In recent years the use of information systems has changed very dramatically. Currently, many information systems are developed for various types of users. These various kinds of users have different characteristics, which makes it very difficult for organizations developing information systems to know the needs of their users. For this reason, a good and in-depth need elicitation is needed to really know the user's needs. The purpose of this study is to explore the needs of users in the E-Learning system of the University of Muhammadiyah Malang to increase user satisfaction of the system. In this study, several elicitation methods were used, namely interviews, storytelling, user personas, and storyboards. The interview method is carried out to explore the problems experienced by users when using the system. Then the results of the interview will be processed into a narrative form of storytelling and then poured into a persona document. By using the above method, you can dig deeper to get a sharper solution to the problems experienced by users. The results of these four methods have proven to be effective in the need elicitation process because these four methods are interrelated and complement each other. This study resulted in a storyboard containing recommended solutions from the results of the excavation of needs carried out on users of the University of Muhammadiyah Malang E-Learning system